THE EFFECT OF THE QUALITY OF BANKING SERVICES ON CUSTOMER SATISFACTION AT PT BANK SUMUT SYARIAH MEDAN BRANCH - Mutholib Mutholib (CERED Indonesia Institute, 2021)
Consumer satisfaction is a person's feelings of pleasure or disappointment arising from comparing performance with product perceptions or results against their expectations. The quality of service is a reflection of the comparison between the level of service delivered by the company compared to customer expectations. This research aims to find out the influence of the quality of banking services provided to customer satisfaction in PT. Bank SUMUT Syariah Medan Branch. The population in this study was customers at Bank SUMUT Syariah Medan branch. The sample is a customer of Bank SUMUT Syariah Medan branch as many as 100 customers. By using axial sampling techniques, namely the determination of samples based on coincidence, i.e. anyone who accidentally met with researchers can be used samples. Data collection techniques in this study are questioner list, interview while the data analysis techniques used are with, ordinary correlation, t test and coefficient of determination. From the correlation coefficient test obtained rxy value = 0.683, which shows a strong influence of service quality on customer satisfaction at PT Bank Sumut Syariah Medan Branch. Based on the t-test obtained thitung > ttabel namely 9,248 > 1,967, then the hypothesis is accepted, so there is a significant influence on the quality of service to customer satisfaction at PT Bank Sumut Syariah Medan Branch. Based on the results of the calculation of coefficient of determination (R2) obtained the value of the coefficient of determination of 46.65%, indicating about 46.65% customer satisfaction can be explained by the quality of service, or practically it can be said that the contribution of service quality to customer satisfaction is 46.65%. The rest is affected by other variables that are not studied.